Pesticide Toxicity Profile: Phosphorous and Sulfur Fumigants - Frederick M. Fishel (EDIS)
This document provides a general overview of human toxicity, a listing of laboratory animal and wildlife toxicities, and a cross reference of chemical, common and trade names of phosphorous and sulfur fumigants registered for use in Florida. This document is PI-73, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published September 2005.